Kepastian Hukum Penerapan Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) - Ramudin, Riko Priyatmo; Ramli, Ahmad M; Rosmana, Hilman (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
Based on the Presidential Regulation on Electronic Government, the Srikandi application (Integrated Records Information System) is part of the General Application for government administration services applied nationally. After three years of implementation, in 2023 the application of Srikandi in Government Institutions (Central and Regional) is not yet optimal. Despite the target that by 2023, all Central Institutions will have implemented Srikandi, and by 2024, all Governments will have implemented Srikandi. The Srikandi application is subject to several regulations, one of which is Law Number 43 of 2009 concerning Archives that has previously regulated matters related to the electronic archival field. Some norms in the Presidential Regulation on SPBE are not harmonious with Law Number 43 of 2009 concerning Archives, especially regarding the substance of archive management, the authority of the National Archives of Indonesia, and the mandate for Srikandi application users. The research method used is Normative Juridical. The research analysis places norms, principles, and legal principles as a study, especially regarding SPBE regulations in the archival services field. The research results show that the mandate of Presidential Regulation Number 95 of 2018 regarding the Electronic Government is not in line with Law Number 43 of 2009 concerning Archives. This is related to norms that regulate the substance of archive management, the authority of archival management, and the users of the Srikandi application. Thus, this creates uncertainty in the implementation of the Srikandi application as a general SPBE application.